THE USE OF MULTILEVEL SENTENCE STRUCTURES AS A STRATEGY TO OVERCOME SYNTACTIC ERRORS IN FOURTH GRADE STUDENTS - Fauziah, Nor Hafizah Indah; Nugraheni, Aninditya Sri; Septiani, Liza (Al-Mubtadi: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study is a literature study that aims to examine the use of multilevel sentence structure as astrategy in overcoming syntactic errors in grade IV elementary school students. The syntax errors in question include the arrangement of phrases, clauses, and sentences that are not in accordance with linguistic rules, such as the use of inappropriate prepositions, the influence of regional languages, and non-standard sentence structures. The factors that cause these errors are divided into two, namely internal factors such as low language skills, interest in reading, and vocabulary mastery; as well as external factors such as lack of habituation to use good and correct language in the study and home environment. Multilevel sentence structures, or multi-level compound sentences, are seen as an effective alternative strategy in overcoming such errors. By introducing semantic relationship patterns such as time and conditions in sentences, students are trained to compose sentences that are more complex and according to syntactic rules. This strategy is aligned with communicative and contextual learning approaches that support the improvement of students' critical thinking skills and writing skills. Based on the results of a literature review, the use of multilevel sentence structure can be an innovative and applicable solution in Indonesian learning in elementary schools.